Immunogenicity and safety of the MF59-adjuvanted seasonal influenza vaccine in non-elderly adults: A systematic review and meta-analysis. - Alexander Domnich; Carlo-Simone Trombetta; Elettra Fallani; Marco Salvatore (PLoS ONE)
Objective In Europe, the age indication for the MF59-adjuvanted quadrivalent influenza vaccine (aQIV) has recently been extended from ≥65 to ≥50 years. Considering that the earliest approval of its trivalent formulation (aTIV) in Italy was for people aged ≥12 years, we aimed to systematically appraise data on the immunogenicity, efficacy, and safety of aTIV/aQIV in non-elderly adults. Methods A systematic literature review was conducted according to the available guidelines and studies were searched in MEDLINE, Biological Abstracts, Web of Science, Cochrane Library and clinical trial registries. Studies on absolute and relative immunogenicity, efficacy, effectiveness, and safety of aTIV/aQIV in non-elderly adults (<65 years) were potentially eligible. These endpoints were analyzed by virus (sub)types and characteristics of vaccinees. Fixed- and random-effects meta-analyses were performed for data synthesis. Protocol registration: CRD42024512472. Results Twenty-four publications were analyzed. aTIV/aQIV was more immunogenic than non-adjuvanted vaccines towards vaccine-like strains: the absolute differences in seroconversion rates were 8.8% (95% CI: 3.7%, 14.0%), 13.1% (95% CI: 6.7%, 19.6%) and 11.7% (95% CI: 7.2%, 16.2%) for A(H1N1), A(H3N2), and B strains, respectively. This immunogenicity advantage was more pronounced in immunosuppressed adults. Additionally, aTIV/aQIV was more immunogenic than non-adjuvanted counterparts towards heterologous A(H3N2) strains with a 10.7% (95% CI: 3.2%, 18.2%) difference in seroconversion rates. Data on antibody persistence and efficacy were limited and inconclusive. Overall, aTIV/aQIV was judged safe and well tolerated, although reactogenic events were more frequent in aTIV/aQIV recipients versus comparators. Serious adverse events were uncommon and no difference (risk ratio 1.02; 95% CI: 0.64, 1.63) between aTIV/aQIV and non-adjuvanted formulations was found. Conclusions In non-elderly adults, aTIV/aQIV is safe and generally more immunogenic than non-adjuvanted standard-dose vaccines.